Research on energy sharing between distribution network and multiple systems based on the mixed game strategy and water-electric-gas integrated energy complementation - Shi, Zhihan; Han, Weisong; Zhang, Guangming; Zhu, Mingxiang; Bai, Zhiqing; Lv, Xiaodong (Frontiers in Energy Research, 2023)
It is significant for energy sharing to study the complementary utilization of multiple energy sources, such as water, electricity and gas, and the interaction among multiple stakeholders. On the one hand, the introduction of the water system, as a new energy source, has broken the coupling effect of the traditional integrated energy system (IES). On the other hand, it is difficult to measure the mixed behaviors of complex plays through a single cooperative game or non-cooperative game methods. Firstly, this paper describes the relationship and functions of all stakeholders under the research framework, and establishes the mathematical model of each unit in the water-electric-gas complementary IES. Secondly, the internal roles are layered based on the relationship between stakeholders in the system. Then a non-cooperative game model for the distribution network operator and multiple subsystems is established according to the theory of Stackelberg game, and a cooperative game model for multiple subsystems is further established based on the theory of Nash bargaining. In the next step, the complexity of the problem is analyzed, followed by the description of the specific algorithm and process of solving the model. Finally, the results of example analysis show that the model proposed in this paper not only balances the interests of stakeholders at the upper and lower layers of the system, but also allocates the interests of multiple subsystems at the lower layer, thus effectively improving the energy utilization of the system.